فاعلية برنامج إرشادي معرفي - سلوكي في تعزيز السلوك الإيجابي عند استخدام وسائل التواصل الاجتماعي لدى طالبات التعليم ما بعد الأساسي بسلطنة عمان - حراصي، علي خلفان حمد
This study aimed to build a cognitive behavioural counselling program and measuring its effectiveness in promoting positive behaviour when using social media among post-basic education female students in the Sultanate of Oman. It also aimed to identify the degree of positive behaviour when using social media among the study sample, as well as revealing the differences among the participants in the counselling program. The researcher adopted the quasi -experimental approach, to reveal the effectiveness of the counselling program. Therefore, he chose a group of (22) students that have distributed equally into two groups, an experimental group to which a collective counseling program was applied, and a control group that did not receive any programs. The program consisted of (14) counseling sessions, each lasting (45) minutes, over eight weeks with two sessions per week. To verify the equivalence of the two groups, the researcher used the t-test in the pre measurement, and calculated the arithmetic averages and standard deviations of the scores of the two groups on the scale of promoting positive behaviour when using social media and on each of its dimensions on each of the measurements; the pre, post and follow-up. The t-test was also used to verify the statistical significance of the differences of the reinforcement of positive behaviour when using social media, as measured by the total score of the scale. The results showed statistically significant differences at the level of significance (α≤0.05) between the pre and post measurements of the experimental group in the total score in favour of the post measurement which indicates that the program is effective in promoting positive behaviour. In addition, the results showed that the impact of the program in the experimental group is significant as it reached (2.46). It also indicated statistically significant differences at the level of significance (α≤0.05) between the experimental and control groups in the total score and in the social, value and ethical dimensions for the post measurement in favour of the experimental group. There were statistically significant differences at the level of significance (α≤0.05) for the experimental group on the total degree of the scale and on the educational and cognitive domains, and in favour of the application of follow-up in the post-measurements and follow-up. It was found that the values of the effect size that were shown by the differences in the dimensional and follow-up measurements for the experimental group in the whole scale and in the educational and cognitive domains amounted to (2.00, 2.02) respectively. This is considered a significant effect according to the Al-Wahaibi, Al-Hadabi and Al-Kharousi criterion, which indicates the continuation of the effectiveness of the counselling program used in this study after a sufficient period.